PH-sensitive polymer-modified liposome-based immunity-inducing system: Effects of inclusion of cationic lipid and CpG-DNA. (October 2017) - Yoshizaki, Yuta; Yuba, Eiji; Sakaguchi, Naoki; Koiwai, Kazunori; Harada, Atsushi; Kono, Kenji
Abstract: Efficient vaccine carriers for cancer immunotherapy require two functions: antigen delivery to dendritic cells (DCs) and the activation of DCs, a so-called adjuvant effect. We previously reported antigen delivery system using liposomes modified with pH-sensitive polymers, such as 3-methylglutarylated hyperbranched poly(glycidol) (MGlu-HPG), for the induction of antigen-specific immune responses. We reported that inclusion of cationic lipids to MGlu-HPG-modified liposomes activates DCs and enhances antitumor effects. In this study, CpG-DNA, a ligand to Toll-like receptor 9 (TLR9) expressing in endosomes of DCs, was introduced to MGlu-HPG-modified liposomes containing cationic lipids using two complexation methods (Pre-mix and Post-mix) for additional activation of antigen-specific immunity. For Pre-mix, thin membrane of lipids and polymers were dispersed by a mixture of antigen/CpG-DNA. For Post-mix, CpG-DNA was added to pre-formed liposomes. Both Pre-mix and Post-mix delivered CpG-DNA to DC endosomes, where TLR9 is expressing, more efficiently than free CpG-DNA solution did. These liposomes promoted cytokine production from DCs and the expression of co-stimulatory molecules in vitro and induced antigen-specific immune responses in vivo . Both Pre-mix and Post-mix exhibited strong antitumor effects compared with conventional pH-sensitive polymer-modified liposomes. Results show that inclusion of multiple adjuvant molecules into pH-sensitive polymer-modified liposomes and suitable CpG-DNA complexation methods are important to design potent vaccine carriers.